When online teacher colleagues meet in person: social-emotional connections and learning at a non-traditional professional convening - Marcelo-Martinez, Paula; Carpenter, Jeffrey P.; Mosquera Gende, Ingrid (Professional Development in Education, 2026)
During their careers, many educators participate in professional conferences. Although formal, face-to-face conferences hosted by education organisations (e.g. professional associations, state education agencies) have a long history, various alternative conference, unconference and meetup formats that blend formal and informal elements, as well as online and offline components, also exist. The knowledge base regarding such non-traditional professional convening formats is, however, limited. This study therefore set out to explore the #EduJornada, a non-traditional conference-like event that has brought together educators in Spain who originally connected primarily online via X (formerly Twitter). Qualitative and quantitative survey data were collected from participants in the second #EduJornada (N=156), and public tweets featuring the #EduJornada hashtag were also gathered. Data analysis found that although many participants affirmed that professional learning occurred at the event, the social-emotional component appeared to be at least as important as knowledge or skill learning. These findings highlight the intertwined cognitive, social, and emotional elements of educators’ professional activities. We discuss the implications of our findings in relation to educator professional development theory, research, and practice.
Keywords: conference; unconference; informal learning; teacher community; teacher networking; social media